2019
DOI: 10.1111/pace.13648
|View full text |Cite
|
Sign up to set email alerts
|

Leadless pacemaker implantation: A feasible and reasonable option in transcatheter heart valve replacement patients

Abstract: Background: Leadless pacemakers (LPMs) have been shown to have lower postoperative complications than traditional permanent pacemakers but there have been no studies on the outcomes of LPMs in patients with transcatheter heart valve replacements (THVRs). This study determined outcomes of LPMs compared to transvenous single-chamber pacemakers (SCPs) post-THVR.Methods: This is a retrospective single-center study including 10 patients who received LPMs post-THVR between February 2017 and August 2018 and a compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Eighty-two studies were further examined in full text, and seven met the pre-specified inclusion criteria (Figure 2). 8,9,11,12,[16][17][18]…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Eighty-two studies were further examined in full text, and seven met the pre-specified inclusion criteria (Figure 2). 8,9,11,12,[16][17][18]…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Previously, Moore et al compared the outcomes between leadless pacing in 10 patients and conventional single-chamber pacing in 23 patients after TAVI. The authors found that the leadless pacemaker performed as well as conventional pacemaker and was associated with less tricuspid regurgitation and less bleeding during the implant procedure [24].…”
Section: Discussionmentioning
confidence: 98%
“…17,27 According to these findings, we should emphasize that patients without baseline characteristics potentially leading to pacemaker dependency should benefit from other temporary leadless system as Micra AV (Medtronic, Minneapolis, Minn) to reduce the rate of permanent pacemaker implanted, as the Micra AV system is recently found to be safe; efficient and as performant as transvenous single-chamber pacemaker. 32,33 Nowadays, guidelines regarding timing of PPI after TAVI are rather cloudy and not based on thorough clinical investigations. 8,34 Due to the lack of consistent data, the dilemma about the appropriate timing for pacemaker implantation after TAVI is left to the discretion of the attending cardiologist according to the different centers' policies and therefore is associated with extreme variability in clinical management.…”
Section: Discussionmentioning
confidence: 99%